Consensual Nonmonogamy in Pregnancy and Parenthood: Experiences of Bisexual and Plurisexual Women With Different-Gender Partners. Issue 8 (17th November 2018) - Manley, Melissa H.; Legge, Melissa M.; Flanders, Corey E.; Goldberg, Abbie E.; Ross, Lori E.
ABSTRACT: The current study constitutes a qualitative investigation of experiences with and perceptions of consensual nonmonogamy (CNM) among a sample of 21 bisexual and plurisexual women with different-gender partners. Participants from Massachusetts, USA, and Toronto, Canada, were interviewed four times during pregnancy and the postpartum period. Using an inductive qualitative approach, we found participants were selective about CNM disclosure, and generally apprehensive about stigma surrounding CNM involvement. Additionally, results emphasize the importance of communication and highlight the range of barriers to and benefits of CNM endorsed by these parents. Directions for future research and implications for practitioners are discussed.